A multilevel boost inverter with removed leakage current and a reduced number of elements for photovoltaic applications - Al-Mamoori, Dalya Hamzah; Azli, Naziha Ahmad; Ayob, Shahrin Md.; Albakry, Ali A. Abdullah (Institute of Advanced Engineering and Science, 2024)
Recent research has concerted on transformer-less multilevel inverters (TL-MLIs) due to their high-voltage or high-power capacity for converting the low-voltage output of renewable energy sources to the desired output. Moreover, they yield higher efficiency, lower cost and size than the conventional type. However, these inverters usually suffer from leakage current. The proposed inverter attempts to accommodate this concern to the greatest extent feasible. The proposed inverter structure exhibits a common ground between the input and output ports. Due to this, the total common mode voltage (CMV) is constant. The photovoltaic (PV) source to the grid parasitic capacitor is short-circuited due to this common ground feature, which results in negligible leakage current. The proposed inverter also features a boosting output voltage using only a single voltage source with minimum power devices. The number of output levels can be increased with the modular application of the proposed inverter. Finally, the mathematical analysis for the proposed inverter has been accomplished, and the MATLAB/Simulink simulation results are presented. Also, the results show the output voltage boost capability, zero leakage current and suitable total harmonic distortion for output voltage and current waveforms.